2013
DOI: 10.1063/1.4819174
|View full text |Cite
|
Sign up to set email alerts
|

Origin of c-axis ultraincompressibility of Zr2InC above 70 GPa via first-principles

Abstract: The elastic and structural properties of nanolaminate Zr 2 InC are studied by first-principles, and it is shown that, for any used modes, including the generalized gradient approximation (GGA) and localized density approximation, there always exists an ultraincompressibility along c axis between 70 GPa and 400 GPa. Such anomalous behavior is originated from the slowdown of core-valence charge transfer. The rapid shift of Zr atom along c axis also contributed much to the ultraincompressibility as it is greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Another important characteristic of the pattern from Cr 2 AlC is the slight shift of these peaks toward lower angles (2θ), which can be explained by continuous expansion of the unit cell along c axis. This phenomenon can be also observed in MAX phases under high pressures due to the structural instabilities and elastic softening, where similar atomic shift was driven by pressure. For V 2 AlC, the occurrence of three new peaks at 39.5°, 41.75°, and 55° (2θ) reveals the phase transition from the original hcp structure to a transformed phase named by γ‐V 2 AlC, which are identified as (002), (101), and (102) peaks [discussed in Section IV ( 2 )].…”
Section: Resultsmentioning
confidence: 54%
“…Another important characteristic of the pattern from Cr 2 AlC is the slight shift of these peaks toward lower angles (2θ), which can be explained by continuous expansion of the unit cell along c axis. This phenomenon can be also observed in MAX phases under high pressures due to the structural instabilities and elastic softening, where similar atomic shift was driven by pressure. For V 2 AlC, the occurrence of three new peaks at 39.5°, 41.75°, and 55° (2θ) reveals the phase transition from the original hcp structure to a transformed phase named by γ‐V 2 AlC, which are identified as (002), (101), and (102) peaks [discussed in Section IV ( 2 )].…”
Section: Resultsmentioning
confidence: 54%
“…At present, Z. J. Yang et al have carried out many theoretical studies on the novel hysteresis behavior of Zr 2 InC based on plane-wave pseudopotential (PW-PP) density functional theory (DFT) calculations, and the mechanical and electronic properties of Zr 2 InC under pressure were investigated using first principles [12]. A.D. Bortolozo et al investigated the Ti 2 InN phase by X-ray diffraction and magnetic and resistivity measurements, and the results clearly showed that Ti 2 InN is the first nitride superconductor belonging to the M n+1 AX n family [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, ternary carbides and nitrides ceramics known as the M n+1 AX n (MAX) phases (where n =1, 2, 3 or higher, M is an early transition metal atom, A is a group , , or elements and X is either C and/or N) have attracted much attention as promising engineering materials, due to their unique properties such as good electrical and thermal conductivity, damage tolerance, high melting point and excellent thermal shock resistance [1][2][3][4][5][6][7][8][9][10][11][12]. According to the value of layer index n, M n+1 AX n phases are labeled as 211, 312 and 413 phases for n=1, 2, 3, respectively.…”
Section: Introductionmentioning
confidence: 99%